Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and sodium ion battery
By using sodium ion battery, sodium ferric pyrophosphate positive electrode material, combined with metal oxide and phosphate doping and carbon cladding technology, the problem of low electrochemical activity of iron-based polyanionic materials is solved, and the battery is improved electrochemical properties and capacity.
Patent Information
- Application Number
- CN202411263496.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing iron-based polyanionic materials have low electrochemical activity and low electrochemical capacity, resulting in poor performance of sodium ion batteries.
Using sodium ferric pyrophosphate positive electrode material, the preset ratio is set between Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7, metal oxide is added as the first conductive agent and phosphate is used as the second conductive agent, and metal cations are doped To enhance the conduction channel and slow down the interface effect through the carbon cladding, improve conductivity and stability.
The electrochemical performance of sodium ion batteries has been significantly improved, the electrochemical specific capacity and stability have been improved, and the 0.1C charging specific capacity has reached 121.6mAh/g.
Smart Images

Figure CN119133442A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium batteries, and in particular relates to a sodium iron pyrophosphate positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] At present, the relatively widely studied materials for positive electrode materials of sodium ion batteries include polyanionic materials. However, the structure of the iron-based polyanionic material NaFePO4 does not have a Na+ transport channel, so it has no electrochemical activity; and the iron-based polyanionic material Na2FeP2O7 has only one Na+ ion that can transport charge, so its electrochemical capacity is relatively low.
[0003] The existing technology has the problem of low electrochemical activity and low electrochemical capacity of iron-based polyanionic materials. Summary of the invention
[0004] The embodiments of the present application provide a lithium iron phosphate positive electrode material and a preparation method thereof, and a sodium ion battery, which aim to solve the problem of low electrochemical activity and low electrochemical capacity of iron-based polyanionic materials to a certain extent.
[0005] In a first aspect, an embodiment of the present application provides a sodium iron phosphate pyrophosphate positive electrode material, wherein the molecular formula of the sodium iron phosphate pyrophosphate positive electrode material is Na4 Fe3(PO4)2P2O7 / D1D2;
[0006] Wherein, D1 is a first conductive agent, the first conductive agent is a metal oxide, the second conductive agent is a phosphate, D2 is a second conductive agent, and the molar ratio of the sodium element, the iron element, the phosphorus element, the first conductive agent and the second conductive agent in the sodium iron pyrophosphate positive electrode material is (4.0-4.1): (2.8-3.0): (3.0-3.1): (0.001-0.0.005): (0.05-0.10);
[0007] The ratio among Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7 in the sodium iron phosphate pyrophosphate positive electrode material is a preset ratio.
[0008] In the embodiment of the present application, compared with the low electrochemical activity and low electrochemical capacity of the iron-based polyanionic material of the prior art, the sodium iron phosphate pyrophosphate positive electrode material is formed according to a preset molar ratio, which reduces the generation of iron phosphate nano-hybrid phases in NaFePO4 and Na2FeP2O7 with low electrochemical activity, and the ratio between Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7 in the sodium iron phosphate pyrophosphate positive electrode material is a preset ratio, wherein the NaFePO4 crystal structure is composed of corner-sharing FeO6 octahedrons and PO4 tetrahedrons, and the Na2FeP2O7 crystal structure is composed of corner-sharing FeO6 octahedrons forming dimers of Fe2O 11 , and is linked with PO4 tetrahedron by sharing corners or edges; the metal cations in the metal oxide of the first conductive agent are embedded in the Fe position of the sodium iron phosphate pyrophosphate positive electrode material. Through the doping of the metal cations at the Fe position, the bond energy between the elements of the two crystal structures can be weakened, and the original crystal structure of NaFePO4 and Na2FeP2O7 is destroyed, thereby increasing the lattice volume, thereby increasing the conduction channel of Na+ and doped ions, and improving the purity of Na4Fe3(PO4)2P2O7 in the sodium iron phosphate pyrophosphate positive electrode material. It has higher electronic conductivity; the phosphate of the second conductive agent forms coating points on the surface of the sodium iron phosphate particles, which slows down the interface effect in the electrochemical reaction process of the sodium iron phosphate pyrophosphate positive electrode material, and slows down the side reaction; and because the Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7 in the sodium iron phosphate pyrophosphate positive electrode material are composed according to a preset ratio, the conductivity can be further improved and the interface effect can be reduced, thereby improving the electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode material and improving the electrochemical specific capacity. After experimental testing, the specific capacity of the sodium ion battery made of the sodium iron phosphate pyrophosphate positive electrode material of the embodiment of the present application is 121.6mAh / g at 0.1C charging.
[0009] In a second aspect, an embodiment of the present application provides a method for preparing the sodium iron phosphate pyrophosphate positive electrode material as described in any one of the first aspects, comprising:
[0010] S1, mixing the sodium element of the sodium source, the iron element of the iron source, the phosphorus element of the phosphorus source, the first conductive agent and the second conductive agent according to a preset molar ratio to obtain a first mixed solution;
[0011] S2, mixing the first mixed solution, the carbon source and water to obtain a second mixed solution;
[0012] S3, grinding the second mixed liquid to a preset particle size and drying to obtain a precursor powder;
[0013] S4, uniformly heating the precursor powder to 500° C. to 700° C., and then keeping the temperature in a protective atmosphere. After the temperature is kept, the precursor powder is crushed by gas to obtain the sodium iron pyrophosphate positive electrode material.
[0014] In the embodiments of the present application, compared with the NaFePO4 generated by the solid phase or liquid phase methods in the prior art, which has no electrochemical activity and Na2FeP2O7, which has only one Na+ that can be deintercalated, since the raw materials of each preset molar ratio are first mixed, ground, dried and granulated in the liquid phase, and then heat-insulated and sintered in a protective atmosphere, the first conductive agent can be effectively doped, and the uniformity of the carbon coating layer on the surface of the sodium iron phosphate pyrophosphate positive electrode material particles is improved in the protective atmosphere, and the second conductive agent forms coating points on the surface of the sodium iron phosphate particles. The carbon coating layer acts as a protective layer to slow down the reaction between the electrolyte and the positive electrode material, thereby enhancing the stability of the positive electrode material, improving the ionic conductivity of the positive electrode material, and providing a more stable electrochemical reaction interface, thereby improving the electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode material.
[0015] In a third aspect, an embodiment of the present application provides a sodium ion battery, wherein the positive electrode of the sodium ion battery comprises the sodium iron phosphate pyrophosphate positive electrode material as described in any one of the first aspect, or the sodium iron phosphate pyrophosphate positive electrode material obtained by the preparation method as described in any one of the second aspect.
[0016] The positive electrode of the sodium ion battery of the embodiment of the present application includes the sodium iron phosphate pyrophosphate positive electrode material in the first aspect, or the sodium iron phosphate pyrophosphate positive electrode material obtained by the preparation method in the second aspect, thereby improving the electrochemical performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 It is a schematic diagram of a process for preparing a sodium iron phosphate pyrophosphate positive electrode material provided in one embodiment of the present application;
[0019] Figure 2 It is a schematic diagram of the 0.1C charge and discharge curves of Experimental Example 1 and Comparative Examples 1, 2, and 3 provided in this application;
[0020] Figure 3 It is a schematic diagram of electron microscope scanning of the sodium iron pyrophosphate positive electrode material of Experimental Example 1 provided in this application;
[0021] Figure 4 It is a schematic diagram of electron microscope scanning of the sodium iron pyrophosphate positive electrode material of comparative example 3 provided in the present application. DETAILED DESCRIPTION
[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0023] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0024] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0025] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0027] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0028] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0029] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0031] In recent decades, with the rapid development of science and technology, traditional fossil fuels have been drastically reduced and it is difficult to meet the growing energy demand. People are eager to find renewable green energy to alleviate this problem. However, the existing green energy has the characteristics of intermittent, regional and climatic. Therefore, the energy storage system that provides stable storage and release for green energy has become the key to the application of green energy. Among them, secondary batteries have become one of the most promising energy storage methods due to their good flexibility and high energy conversion efficiency. In particular, lithium-ion batteries have been rapidly developed due to their high energy density, high voltage and long cycle life. Since the first commercialization of lithium-ion batteries, they have been successfully applied in portable devices, grid storage, electric vehicles and hybrid vehicles. With the support of the state for new energy vehicles in recent years, the demand for lithium batteries has soared, resulting in the rising price of lithium and the increasingly serious problem of lithium resource scarcity. Therefore, people have turned their attention to sodium-ion batteries with slightly lower energy density. Due to the wide source of sodium, similar physical and chemical properties to lithium, and unique advantages in safety, it is expected to become the best substitute for lithium-ion batteries in the field of fixed energy storage.
[0032] At present, the materials that are relatively widely studied in the positive electrode materials of sodium ion batteries include layered transition metal oxides and polyanionic materials. Layered transition metal oxides have high specific capacity due to their reversible ion deintercalation ability and stable layered structure, but the electrochemical cycle performance of the material is poor and the discharge voltage is low, making it difficult to improve the energy density of the material; and the iron-based polyanionic material NaFePO4 has no Na+ transport channel in its structure, so it has no electrochemical activity; in the iron-based polyanionic material Na2FeP2O7, only one Na+ can be deintercalated in the electrochemical reaction. Since only one Na+ ion can carry out charge transfer, the electrochemical capacity is low, and the charge-discharge specific capacity is only 97.2mAh / g.
[0033] In order to solve the technical problems of low electrochemical activity and low electrochemical capacity of iron-based polyanionic materials to a certain extent, the first aspect of the embodiment of the present application provides a sodium iron pyrophosphate positive electrode material, the molecular formula of the sodium iron pyrophosphate positive electrode material is Na4 Fe3(PO4)2P2O7 / D1D2, wherein D1 is a first conductive agent, the first conductive agent is a metal oxide, the second conductive agent is a phosphate, and D2 is a second conductive agent. The molar ratio of sodium element, iron element, phosphorus element, first conductive agent and second conductive agent in the sodium iron pyrophosphate positive electrode material is (4.0-4.1):(2.8-3.0):(3.0-3.1):(0.001-0.0.005):(0.05-0.10); the ratio between Na4Fe3(PO4)2P2 O7, NaFePO4 and Na2FeP2O7 in the sodium iron pyrophosphate positive electrode material is a preset ratio.
[0034] In the embodiment of the present application, compared with the low electrochemical activity and low electrochemical capacity of the iron-based polyanionic material of the prior art, the sodium iron phosphate pyrophosphate positive electrode material is formed according to a preset molar ratio, which reduces the generation of iron phosphate nano-hybrid phases in NaFePO4 and Na2FeP2O7 with low electrochemical activity, and the ratio between Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7 in the sodium iron phosphate pyrophosphate positive electrode material is a preset ratio, wherein the NaFePO4 crystal structure is composed of corner-sharing FeO6 octahedrons and PO4 tetrahedrons, and the Na2FeP2O7 crystal structure is composed of corner-sharing FeO6 octahedrons forming dimers of Fe2O 11 , and is linked with PO4 tetrahedron by sharing corners or edges; the metal cations in the metal oxide of the first conductive agent are embedded in the Fe position of the sodium iron pyrophosphate positive electrode material. The metal cation doping at the Fe position can weaken the bond energy between the elements of the two crystal structures, destroying the original crystal structure of NaFePO4 and Na2FeP2O7, thereby increasing the lattice volume, and then increasing the conduction channel of Na+ and doped ions, with higher electronic conductivity; the phosphate of the second conductive agent forms a coating on the surface of the sodium iron phosphate particles, slowing down the formation of the sodium iron pyrophosphate positive electrode material. The interface effect during the electrochemical reaction of the electrode material slows down the side reaction; and because Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7 in the sodium iron phosphate pyrophosphate positive electrode material are composed according to a preset ratio, the conductivity can be further improved and the interface effect can be reduced, thereby improving the electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode material and increasing the electrochemical specific capacity; at the same time, due to the inductive effect of phosphate anions (PO4) with a higher redox potential and the presence of a polyanion structure framework, it is beneficial to maintain structural stability during the sodium ion deintercalation process.
[0035] In one embodiment, the preset ratio between Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7 is (85-95):(2-15):(3-5), and the preset ratio is a preset molar ratio. The sodium iron phosphate pyrophosphate positive electrode material composed of the preset ratio in this embodiment reduces the occupancy ratio of NaFePO4 and Na2FeP2O7, and destroys the original crystal structure of NaFePO4 and Na2FeP2O7 due to doping, thereby increasing the conduction channels of Na+ and doped ions, thereby improving the electronic conductivity of the sodium iron phosphate pyrophosphate positive electrode material.
[0036] In one embodiment, the molar ratio between the sodium element and the iron element in the sodium iron pyrophosphate positive electrode material is 4:(2.90-2.95). After experimental testing, the specific capacity of the sodium ion battery made of the sodium iron pyrophosphate positive electrode material of the embodiment of the present application at 0.1C charging reaches 121.6 mAh / g, which is within the theoretical specific capacity range of 120 mAh / g to 128 mAh / g for the sodium iron pyrophosphate positive electrode material.
[0037] In one embodiment, the mass ratio of the total mass of the sodium source, the iron source, the phosphorus source, the first conductive agent, the second conductive agent and the carbon source to the water is (1-3):(1-7). The mass ratio of this embodiment can control the concentration of the suspension to avoid the effect of too low or too high concentration on the preparation of the sodium iron pyrophosphate positive electrode material.
[0038] In one embodiment, the particle size D50 of the sodium iron phosphate pyrophosphate positive electrode material is 0.6 μm to 1.5 μm. The particle size D50 range of this embodiment can increase the compaction density of the sodium iron phosphate pyrophosphate positive electrode material.
[0039] In one embodiment, the iron source includes at least one of ferric phosphate, ferric oxide, ferrous oxalate, iron powder, and ferric nitrate; and / or, the sodium source includes at least one of sodium carbonate, trisodium phosphate, sodium acetate, sodium acetate, sodium oxalate, sodium bicarbonate, or sodium sulfate; and / or, the phosphorus source includes at least one of diammonium phosphate, ammonium phosphate, lithium phosphate, phosphoric acid, and iron phosphate; and / or, the carbon source includes at least one of acetylene black, Ketjen black, glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol, and polyaniline; and / or, the first conductive agent includes at least one of vanadium pentoxide, magnesium oxide, aluminum oxide, and titanium oxide; and / or, the second conductive agent includes at least one of lithium phosphate, aluminum phosphate, and manganese phosphate. This embodiment defines the sources of the iron source, the sodium source, the phosphorus source, the carbon source, the first conductive agent, and the second conductive agent, and can synthesize a sodium iron phosphate pyrophosphate positive electrode material with high purity, stable electrochemical reaction, and high specific capacity, and can also be replaced with other materials to reduce production costs when any of the materials is in short supply.
[0040] In a second aspect, an embodiment of the present application provides a method for preparing the sodium iron phosphate pyrophosphate positive electrode material as described in any one of the first aspects, comprising:
[0041] S1, mixing the sodium element of the sodium source, the iron element of the iron source, the phosphorus element of the phosphorus source, the first conductive agent and the second conductive agent according to a preset molar ratio to obtain a first mixed solution;
[0042] S2, mixing the first mixed solution, the carbon source and water to obtain a second mixed solution;
[0043] S3, grinding the second mixed liquid to a preset particle size and drying to obtain a precursor powder;
[0044] S4, uniformly heating the precursor powder to 500° C. to 700° C., and then keeping the temperature in a protective atmosphere. After the temperature is kept, the precursor powder is crushed by gas to obtain a sodium iron pyrophosphate positive electrode material.
[0045] In the embodiments of the present application, compared with the NaFePO4 generated by the solid phase or liquid phase methods in the prior art, which has no electrochemical activity and Na2FeP2O7, which has only one Na+ that can be deintercalated, since the raw materials of each preset molar ratio are first mixed, ground, dried and granulated in the liquid phase, and then heat-insulated and sintered in a protective atmosphere, the first conductive agent can be effectively doped, and the uniformity of the carbon coating layer on the surface of the sodium iron phosphate pyrophosphate positive electrode material particles is improved in the protective atmosphere, and the second conductive agent forms coating points on the surface of the sodium iron phosphate particles. The carbon coating layer acts as a protective layer to slow down the reaction between the electrolyte and the positive electrode material, thereby enhancing the stability of the positive electrode material, improving the ionic conductivity of the positive electrode material, and providing a more stable electrochemical reaction interface, thereby improving the electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode material.
[0046] In one embodiment, the grinding method is ball milling first and then sand milling; the particle size D50 of the incompatible particles in the second mixed solution after ball milling is 2.0 μm to 5.0 μm; the particle size D50 of the incompatible particles in the second mixed solution after sand milling is 0.4 μm to 1.0 μm. Using the grinding method of this embodiment, sand milling after ball milling can successively reduce the particle size of the incompatible particles in the second mixed solution.
[0047] In one embodiment, the parameters of ball milling are: the ball milling temperature is 25℃~35℃, the ball milling time is 0.5h~4h, and the ball milling speed is 800rpm~2000rpm; and / or, the parameters of sand milling are: the sand milling temperature is 25℃~35℃, the sand milling time is 0.5h~4h, and the sand milling speed is 5000rpm~10000rpm; and / or, the drying is spray drying; the air inlet temperature during the spray drying process is 200℃~300℃, and the air outlet temperature is 90℃~120℃. The parameters of ball milling and sand milling of this embodiment can grind the insoluble matter in the second solution to the required particle size and maintain the consistency of the particle size; the spray drying and the spray drying parameters of this embodiment can form a precursor powder with uniform particle size.
[0048] In one embodiment, the holding time in step S4 is 8h to 12h; the holding time of this embodiment can make the doping of the first conductive agent, the coating layer of the carbon source and the point coating reaction of the second conductive agent more complete, thereby improving the electrochemical performance of the sodium iron pyrophosphate positive electrode material.
[0049] In one embodiment, the protective atmosphere includes a protective gas; the protective gas includes at least one of nitrogen or argon; the use of the inert gas of this embodiment improves the uniformity of the carbon coating layer on the surface of the sodium iron pyrophosphate positive electrode material particles.
[0050] In one embodiment, the protective atmosphere further comprises a reducing gas; the reducing gas comprises at least one of carbon monoxide or hydrogen; the volume of the reducing gas accounts for 2% to 8% of the total volume of the protective atmosphere. The reducing gas of this embodiment can reduce part of the cations in the conductive agent, thereby increasing the doping concentration of the metal cations and improving the conductivity of the sodium iron pyrophosphate positive electrode material.
[0051] In a third aspect, an embodiment of the present application provides a sodium ion battery, wherein the positive electrode of the sodium ion battery comprises the sodium iron phosphate pyrophosphate positive electrode material as described in any one of the first aspect, or the sodium iron phosphate pyrophosphate positive electrode material obtained by the preparation method as described in any one of the second aspect.
[0052] The positive electrode of the sodium ion battery of the embodiment of the present application includes the sodium iron phosphate pyrophosphate positive electrode material in the first aspect, or the sodium iron phosphate pyrophosphate positive electrode material obtained by the preparation method in the second aspect, thereby improving the electrochemical performance of the sodium ion battery.
[0053] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0054] Experimental Example 1
[0055] This embodiment provides a method for preparing a sodium iron phosphate material, comprising:
[0056] Step 1), 10 kg of FePO4, 4.94 kg of trisodium phosphate, 0.028 kg of titanium oxide, and 0.86 kg of lithium phosphate are placed in a 50 L stainless steel stirred mill and mixed, and then 0.15 kg of glucose and 0.15 kg of polyethylene glycol are added, and then 20 L of water is added and ball-milled at 25 ° C at a speed of 1000 rpm for 1 hour to obtain a ball-milled mixed solution, wherein the D50 of the particles of the insoluble matter in the ball-milled mixed solution is 3.5 ± 0.20 μm, and the molar ratio of the iron element of FePO4 to the sodium element of trisodium phosphate is 4:2.93;
[0057] Step 2), transferring the ball-milled mixed solution into a sand mill, and sand milling the mixed solution at 8000 rpm for 1 h at 25° C. to obtain a sand-milled mixed solution, wherein the D50 of the particles of the insoluble matter in the sand-milled mixed solution is 0.3±0.10 μm;
[0058] Step 3), spray drying the mixed solution after sand milling to obtain a precursor powder, wherein the air inlet temperature during the spray drying process is 300° C. and the air outlet temperature is 200° C.;
[0059] Step 4), placing the obtained precursor powder in a tubular furnace, uniformly heating to 550° C. in a nitrogen atmosphere for 6 hours, and then sintering at 650° C. for 10 hours to obtain a sodium iron pyrophosphate positive electrode material.
[0060] Experimental Example 2: The difference from Experimental Example 1 is that the raw materials and quality in step 1) are changed
[0061] Step 1), 10kg of FePO4, 7.425kg of sodium acetate, 4.915kg of phosphoric acid, 0.053kg of titanium oxide, and 0.78kg of aluminum phosphate are placed in a 50L stainless steel stirred mill and mixed, and then 0.15kg of glucose and 0.15kg of polyethylene glycol are added, and then 20L of water is added and ball-milled at 25°C at a speed of 1000rpm for 1h to obtain a ball-milled mixed solution, wherein the D50 of the particles of the insoluble matter in the ball-milled mixed solution is 3.5±0.20μm, and the molar ratio of the iron element of FePO4 to the sodium element of trisodium phosphate is 4:2.93.
[0062] Comparative Example 1: The difference from Experimental Example 1 is that the amount of trisodium phosphate is changed and the molar ratio of iron to sodium is changed.
[0063] Step 1), 10kg of FePO4, 5.121kg of trisodium phosphate, 0.028kg of titanium oxide, and 0.86kg of lithium phosphate are charged into a 50L stainless steel stirred mill and mixed, and then 0.15kg of glucose and 0.15kg of polyethylene glycol are added, and then 20L of water is added and ball-milled at 25°C at a speed of 1000rpm for 1h to obtain a ball-milled mixed solution, wherein the D50 of the particles of the insoluble matter in the ball-milled mixed solution is 3.5±0.20μm, and the molar ratio of the iron element of FePO4 to the sodium element of trisodium phosphate is 4:2.83.
[0064] Comparative Example 2: The difference from Experimental Example 1 is that the amount of trisodium phosphate is changed and the molar ratio of iron to sodium is changed.
[0065] Step 1), 10kg of FePO4, 4.831kg of trisodium phosphate, 0.028kg of titanium oxide, and 0.86kg of lithium phosphate are placed in a 50L stainless steel stirred mill and mixed, and then 0.15kg of glucose and 0.15kg of polyethylene glycol are added, and then 20L of water is added and ball-milled at 25°C at a speed of 1000rpm for 1h to obtain a ball-milled mixed solution, wherein the D50 of the particles of the insoluble matter in the ball-milled mixed solution is 3.5±0.20μm, and the molar ratio of the iron element of FePO4 to the sodium element of trisodium phosphate is 4:3.
[0066] Comparative Example 3: The difference from Experimental Example 1 is that the second conductive agent lithium phosphate is not added
[0067] Step 1), 10kg of FePO4, 4.831kg of trisodium phosphate, and 0.028kg of titanium oxide are placed in a 50L stainless steel stirred mill and mixed, and then 0.15kg of glucose and 0.15kg of polyethylene glycol are added, and then 20L of water is added and ball-milled at 25°C at a speed of 1000rpm for 1h to obtain a ball-milled mixed solution, wherein the D50 of the particles of the insoluble matter in the ball-milled mixed solution is 3.5±0.20μm, and the molar ratio of the iron element of FePO4 to the sodium element of trisodium phosphate is 4:3.
[0068] The sodium iron phosphate pyrophosphate positive electrode materials of Experimental Examples 1 and 2 and Comparative Examples 1, 2, and 3 were respectively made into button batteries, and the specific capacity of charge and discharge at 0.1C was tested. The test data are shown in Table 1. Figure 2 As shown; the sodium iron phosphate pyrophosphate positive electrode materials of Experimental Example 1 and Comparative Example 3 were observed using a scanning electron microscope, and the scanning electron microscope images were as shown Figure 3 , Figure 4 shown.
[0069] Table 1 Specific capacity of sodium iron phosphate pyrophosphate positive electrode materials at 0.1C for charge and discharge
[0070] sample 0.1C charging capacity mAh / g 0.1C discharge capacity mAh / g Experimental Example 1: Iron-sodium ratio is 4:293 121.6 115.2 Experimental Example 2: Iron-sodium ratio is 4:293 120.8 114.6 Comparative Example 1: Iron-sodium ratio is 4:283 111.6 105.5 Comparative Example 2: Iron-sodium ratio is 4:3 108.7 103.1 Comparative Example 3: Adding a second conductive agent 102.4 97.6
[0071] By comparing the data in Table 1, the addition of the second conductive agent of the metal-coated conductive material increases the specific capacity of the sodium iron pyrophosphate positive electrode material; by comparing the charge data of Experiment 1 with Comparative Example 1 and Comparative Example 2, the specific capacity of the sodium iron pyrophosphate positive electrode material is the highest when the molar ratio of iron to sodium is 4:293, and after the molar ratio of iron to sodium is 4:3, according to Figure 2 It was found that there was a voltage change in the charging curve of Comparative Example 2 and the voltage platform of the discharge curve increased more significantly. This may be due to an irreversible phase change during the electrochemical reaction, which led to the dissolution of Na / Fe, thereby increasing its voltage platform. The dissolution of Na / Fe will cause continuous attenuation during the cycle process, affecting the safety of the battery.
[0072] contrast Figure 3 Schematic diagram of electron microscope scanning of Experimental Example 1 and Figure 4 The electron microscope scanning diagram of Comparative Example 3 shows that there is a coating layer on the surface of the sodium iron pyrophosphate positive electrode material of Experimental Example 1. The coating layer slows down the interfacial effect in the electrochemical reaction of the sodium iron pyrophosphate positive electrode material and improves the electrochemical performance of the material.
[0073] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0074] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The molecular formula of the sodium iron phosphate pyrophosphate positive electrode material is Na4 Fe3(PO4)2P2O7 / D1D2; Wherein, D1 is a first conductive agent, the first conductive agent is a metal oxide, the second conductive agent is a phosphate, D2 is a second conductive agent, and the molar ratio of the sodium element, the iron element, the phosphorus element, the first conductive agent and the second conductive agent in the sodium iron pyrophosphate positive electrode material is (4.0-4.1): (2.8-3.0): (3.0-3.1): (0.001-0.0.005): (0.05-0.10); The ratio among Na4Fe3(PO4)2P2O7, NaFePO4 and Na2FeP2O7 in the sodium iron phosphate pyrophosphate positive electrode material is a preset ratio.
2. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that The mass ratio of the total mass of the sodium source, the iron source, the phosphorus source, the first conductive agent, the second conductive agent and the carbon source to the mass of the water is (1-3):(1-7).
3. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that The particle size D50 of the sodium iron phosphate pyrophosphate positive electrode material is 0.6 μm to 1.5 μm.
4. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that The iron source includes at least one of ferric phosphate, ferric oxide, ferrous oxalate, iron powder, and ferric nitrate; and / or, the sodium source comprises at least one of sodium carbonate, trisodium phosphate, sodium acetate, sodium acetate, sodium oxalate, sodium bicarbonate, or sodium sulfate; and / or, the phosphorus source includes at least one of diammonium phosphate, ammonium phosphate, lithium phosphate, phosphoric acid, and iron phosphate; And / or, the carbon source comprises at least one of acetylene black, Ketjen black, glucose, sucrose, fructose, citric acid, starch, polyvinyl alcohol, polyethylene glycol, and polyaniline; And / or, the first conductive agent includes at least one of vanadium pentoxide, magnesium oxide, aluminum oxide, and titanium oxide; And / or, the second conductive agent includes at least one of lithium phosphate, aluminum phosphate, and manganese phosphate.
5. A method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 1 to 4, characterized in that: include: S1, mixing the sodium element of the sodium source, the iron element of the iron source, the phosphorus element of the phosphorus source, the first conductive agent and the second conductive agent according to a preset molar ratio to obtain a first mixed solution; S2, mixing the first mixed solution, the carbon source and water to obtain a second mixed solution; S3, grinding the second mixed liquid to a preset particle size and drying to obtain a precursor powder; S4, uniformly heating the precursor powder to 500° C. to 700° C., and then keeping the temperature in a protective atmosphere. After the temperature is kept, the precursor powder is crushed by gas to obtain the sodium iron pyrophosphate positive electrode material.
6. The preparation method according to claim 1, characterized in that: The grinding method is ball milling first and then sand milling; The particle size D50 of the insoluble particles in the second mixed solution after ball milling is 2.0 μm to 5.0 μm; The particle size D50 of the insoluble particles in the second mixed liquid after the sand grinding is 0.4 μm to 1.0 μm.
7. The preparation method according to claim 4, characterized in that: The parameters of the ball milling are as follows: the ball milling temperature is 25°C to 35°C, the ball milling time is 0.5h to 4h, and the ball milling speed is 800rpm to 2000rpm; And / or, the parameters of the sanding are: the sanding temperature is 25° C. to 35° C., the sanding time is 0.5 h to 4 h, and the sanding speed is 5000 rpm to 10000 rpm; And / or, the drying is spray drying; during the spray drying process, the air inlet temperature is 200°C to 300°C, and the air outlet temperature is 90°C to 120°C.
8. The preparation method according to claim 1, characterized in that: The protective atmosphere includes a protective gas; the protective gas includes at least one of nitrogen or argon.
9. The preparation method according to claim 1, characterized in that: The protective atmosphere also includes reducing gas; the reducing gas includes at least one of carbon monoxide and hydrogen; the volume of the reducing gas accounts for 2% to 8% of the total gas volume of the protective atmosphere.
10. A sodium ion battery, characterized in that: The positive electrode of the sodium ion battery comprises the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 1 to 4, or the sodium iron phosphate pyrophosphate positive electrode material obtained by the preparation method according to any one of claims 5 to 9.
Citation Information
Cited By
Electrode material, preparation method thereof and sodium ion hybrid capacitor
CN120854186A
Porous composite electrode material and preparation method and application thereof
CN121416445A
Sodium-ion battery monomer, preparation method thereof, battery device and power utilization device
CN121583993A
Positive electrode material, and preparation method therefor and use thereof
WO2026144109A1
